Role of PKCtheta in macrophage-mediated immune response to Salmonella typhimurium infection in mice. Issue 1 (December 2016) - Pfeifhofer-Obermair, Christa; Albrecht-Schgoer, Karin; Peer, Sebastian; Nairz, Manfred; Siegmund, Kerstin; Klepsch, Victoria; Haschka, David; Thuille, Nikolaus; Hermann-Kleiter, Natascha; Gruber, Thomas; Weiss, Günter; Baier, Gottfried
Abstract Background The serine/threonine protein kinase C (PKC) theta has been firmly implicated in T cell-mediated immunity. Because its role in macrophages has remained undefined, we employedPKCtheta -deficient (PKCtheta −/− ) mice in order to investigate if PKCtheta plays a role in macrophage-mediated immune responses during bacterial infections. Results Our results demonstrate that PKCtheta plays an important role in host defense against the Gram-negative, intracellular bacteriumSalmonella typhimurium, as reflected both by markedly decreased survival and a significantly enhanced number of bacteria in spleen and liver ofPKCtheta −/− mice, when compared to wild-type mice. Of note, albeit macrophages do not express detectable PKCtheta, PKCtheta mRNA expression was found to be profoundly upregulated during the first hours of lipopolysaccharide (LPS)/interferon-gamma (IFNgamma)-, but not IL-4-mediated cell polarization conditions in vitro. Mechanistically, despite expressing normal levels of classically activated macrophage (CAM) markers, PKCtheta -deficient CAMs expressed significantly higher levels of the anti-inflammatory cytokine IL-10 in vivo and in vitro when challenged withS. typhimurium or LPS/IFNgamma. Neutralization of IL-10 recovered immune control toS. typhimurium infection inPKCtheta -deficient macrophages. Conclusions Taken together, our data provide genetic evidence that PKCtheta promotes a potent pro-inflammatory CAM phenotype that is instrumental to mounting protective anti-bacterial immunity. Mechanistically, PKCtheta exerts a host-protective role againstS. typhimurium infection, and acts as an essential link between TLR4/IFNgammaR signaling and selective suppression of the anti-inflammatory cytokine IL-10 at the onset of CAM differentiation in the course of a bacterial infection.